Explique passo a passo
![Explique Passo A Passo class=](https://pt-static.z-dn.net/files/dc3/ef6c2b89bc51f3c394356633673a319f.jpg)
Resposta:
-75/28
[tex] \frac{3 \times ( - \frac{1}{2} )+ \frac{1}{4} }{3 \times ( - \frac{1}{3}) ^{2} - \frac{3}{2} } = \\ \frac{ - \frac{3}{2} + \frac{1}{4} }{3 \times ( \frac{1}{9} )- \frac{3}{2} } = \\ \frac{ - \frac{6}{4} + \frac{1}{4} }{ \frac{3}{9} - \frac{3}{2} } = \\ \frac{ \frac{ - 5}{4} }{ \frac{1}{3} - \frac{3}{2} } = \\ \frac{ \frac{ - 5}{4} }{ \frac{2}{6} - \frac{9}{6} } = \\ \frac{ \frac{ - 5}{4} }{ \frac{ - 7}{6} } = \\ \frac{ - 5}{4} \times \frac{ - 6}{7} = \\ \frac{30}{28} = \frac{15}{14} [/tex]
substituir valor de A
[tex] \frac{ \frac{15}{14} }{2} - 3 \times \frac{15}{14} = \\ \frac{15}{14} \times \frac{1}{2} - \frac{45}{14} = \\ \frac{15}{28} - \frac{45}{14} = \\ \frac{15}{28} - \frac{90}{28} = - \frac{75}{28} [/tex]